2005
DOI: 10.1016/j.ijid.2004.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment options for hepatic cystic echinococcosis

Abstract: A number of surgical and non-surgical options exist to treat cystic echinococcosis of the liver. For decades, surgical excision via a conservative or radical approach was the recommended approach for hepatic hydatid cysts. The availability of chemotherapeutic agents with significant activity against Echinococcus granulosis has made it possible to undertake ultrasound- or computed tomography-guided transhepatic percutaneous drainage (termed puncture, aspiration, injection, and re-aspiration (PAIR)) of hydatid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
152
0
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(171 citation statements)
references
References 60 publications
5
152
0
8
Order By: Relevance
“…Similarly, recurrence was recorded in 8 patients who underwent the PAIR technique in the present study. Although some authors state that the PAIR technique is contraindicated due to potential anaphylaxis and spillage of scolices (12) , other investigators have reported neither anaphylaxis nor dissemination with the PAIR technique (29) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, recurrence was recorded in 8 patients who underwent the PAIR technique in the present study. Although some authors state that the PAIR technique is contraindicated due to potential anaphylaxis and spillage of scolices (12) , other investigators have reported neither anaphylaxis nor dissemination with the PAIR technique (29) .…”
Section: Discussionmentioning
confidence: 99%
“…Instead of surgical removal, one recommended therapeutic procedure for hepatic hydatid cysts is the PAIR technique, which involves needle aspiration and concurrent chemotherapy (12) and satisfi es all of the surgical goals for hydatid disease by sclerosing the germinal membrane and separating the laminated membrane with scolicides (13) . However, the mainstay of therapy METHODS currently consists of well-planned surgical techniques and appropriate procedures based on the correct evaluation of disease complications and performed by an experienced team, with adequate postoperative support (14) .…”
mentioning
confidence: 99%
“…Traveling and tourism has change its pattern to a wide spread disease even in developed countries. [1][2][3][4] Hydatid cyst has been treated using medical treatment and cutaneous drainage and surgery, [5][6][7][8] but the main treatment has been surgery using different techniques which generally is divided in two subgroups; radical one and conservative. [9][10][11] Using conservative procedure, the cyst would be drained out without omitting the pericystial layer; while radical procedure focuses on removing all the cyst layers as well as percystial one.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Using conservative procedure, the cyst would be drained out without omitting the pericystial layer; while radical procedure focuses on removing all the cyst layers as well as percystial one. [2,3,7,12] Conservative therapies are simple and safe procedures but comparing to radical one post operative complications, recurrence and hospital stay time are higher. [12][13][14][15] In this study 135 patients with hydatid cyst have been retrospectively evaluated during 10 years of experience and the outcomes of different techniques have been compared to see if the radical therapy has less complications and recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors affect the preference of therapeutic surgical approach including number and localization of the cysts, surgeon expertise and presence of complications. One of the recommended therapeutic procedures for hepatic hydatid cysts is needle aspiration and concurrent chemotherapy known as the PAIR procedure to be done instead of surgical removal [9,12]. The PAIR procedure is recorded to satisfy all the goals of surgery for hydatid disease by sclerosing germinal membrane and separating laminated membrane with scolicides [13].…”
Section: Introductionmentioning
confidence: 99%